THE RELATIONSHIP BETWEEN PREGNANT WOMEN'S EDUCATION LEVEL AND THE INCIDENCE OF PREECLAMPSIA IN THE WORKING AREA OF PENANA'E PUBLIC HEALTH CENTER IN 2026 - Yati Purnama; Sri Astuti; Ainun Korimah (STMIK Indonesia Banda Aceh, 2026)
Preeclampsia is one of the leading causes of maternal morbidity and mortality in Indonesia. One of the factors associated with the incidence of preeclampsia is the educational level of pregnant women. A low educational level may affect a mother's ability to obtain, understand, and apply information regarding maternal health, thereby increasing the risk of developing preeclampsia. This study aimed to determine the relationship between the educational level of pregnant women and the incidence of preeclampsia in the working area of Penana'e Community Health Center, Bima City, in 2026. This study employed a quantitative method with an analytical observational design using a cross-sectional approach. The study population consisted of all pregnant women who attended antenatal care services at the Penana'e Community Health Center. A total of 73 respondents were selected using the total sampling technique. Data were analyzed using univariate and bivariate analyses with the Chi-Square test at a significance level of α = 0.05. The results showed that the majority of respondents had a basic educational level (elementary and junior high school), accounting for 46 respondents (63.0%). The incidence of preeclampsia was found in 32 respondents (43.8%), consisting of 20 respondents (27.4%) with mild preeclampsia and 12 respondents (16.4%) with severe preeclampsia, while 41 respondents (56.2%) did not experience preeclampsia. The Chi-Square test yielded a p-value of 0.005 (p < 0.05), indicating a significant relationship between the educational level of pregnant women and the incidence of preeclampsia. It can be concluded that pregnant women with lower educational attainment are at a higher risk of developing preeclampsia than those with higher educational levels. Therefore, strengthening maternal health education and promoting early detection during pregnancy are essential to reduce the risk of preeclampsia and improve maternal and fetal health outcomes.